Investment policy factors of enterprises in Serbia: Agriculture and processing industry sectors - Aničić Jugoslav; Vukotić Svetlana; Aničić Dušan; Petrović Vesna; Čavić Dejan (Ekonomika Poljoprivrede (1979), 2021)
In this paper, the authors research and analyze the impact of factors that decisively influence making investment decisions in enterprises operating in the agriculture and processing industry sectors. The fact is that significant foreign direct investments have been coming to Serbia for many years, but the development gap with comparable countries in Central and Eastern Europe is not decreasing. Analysis show that economic development cannot be left only to the market and foreign investments, but an appropriate economic policy is needed to encourage public and private investments, based on domestic savings. Authors believe that companies from agriculture and processing industry should be carriers of economic growth and development, employment, exports and the creation of new value, but they need a stable and predictable business environment, as well as the support of official economic policy.